Formulation and Implementation of Sharia Bank Development Strategy in the Dynamics of National Banking Competition - Dainori; Tamimah (PT Bukuloka Literasi Bangsa, 2026)
Abstract This study analyzes the formulation and implementation of Islamic bank development strategies within the context of increasingly intense national banking competition. The primary focus is on identifying internal and external factors influencing Islamic bank competitiveness, including regulatory developments, market penetration, product and service innovation, and changing customer preferences. This study uses a qualitative approach using literature review and policy analysis, incorporating a strategic management framework to assess the effectiveness of strategies implemented by Islamic banks. The results indicate that the success of Islamic bank development is largely determined by the institution's ability to formulate a differentiation strategy based on Islamic values, strengthen digital capabilities, and build strategic partnerships with various stakeholders. The implementation of strategies that are adaptive and responsive to market dynamics has been shown to significantly impact performance improvements, operational effectiveness, and public trust. These findings provide conceptual and practical contributions to strengthening the competitiveness of Islamic banks in a competitive national banking ecosystem. Keywords: Development Strategy, Islamic Banks, Strategic Management, Banking Competition, Service Innovation, Banking Regulations.